Lenin's last struggle / Moshe Lewin ; translated from the French by A. M. Sheridan Smith - Lewin, Moshe (1921-2010) (Vintage books ; 587)
Índice onománstico con datos biográficos: p.177-180Apéndice documental: p. 146-176